QUALITATIVE EVALUATION OF THE URBAN VEGETATION IN TANCREDO NEVES HABITATIONAL CONJUNCT, SANTA MARIA, RIO GRANDE DO SUL STATE - Teixeira, Italo Filippi (1999)
Tancredo Neves area, Santa Maria, RS, a census was conducted with the objective of investigating the urban vegetation of its streets and avenues thus allowing the qualitative evaluation of its vegetation components. From 112 vegetal species, which account for 2,778 units distributed irregularly, 14 species totalized 70, 6 of the total. Most of them have a new dimension, are in the seedling, stage and are not under any spinning. The prevailing area is limited, with a deep radicular system without causing any damage, and a satisfactory phyto-sanitary condition. The patterns regarding its distance from the curb and buildings and walls are in accordance with the literature. Only the distance from the lampposts is not accordance with these principles. The most frequent treatment needed consists of pruning the tree lightly (43,3%). Most of the damages were caused by pruning (46,0%) which is done by local inhabitants. The vegetables are compatible, in their great majority (44,9%) to the equipments and buildings.